The Phenomenon of the 18th Century Institutional Printing House of the Grand Duchy of Lithuania: The Case of the Franciscans - Kažuro, Ina (Knygotyra, 2021)
Many of the printing houses in the Grand Duchy of Lithuania that operated during the 17th-18th centuries belonged to institutions the biggest part of which consisted of Catholic monk monasteries. Despite belonging to one group, the development path of each printing house and its contribution to book culture has unique features. Of the four institutional printing houses operating in the 18th century in Vilnius, the printing house of the Franciscan Conventuals Monastery was the first to be closed and its operations terminated. The purpose of the article is to identify the following causes behind the issues and eventual closure of this printing house. Based on the expenses and income book of this printing house for the period 1752–1769 (it is preserved at the Department of Manuscripts of Vilnius University Library,) this paper examines various aspects of the Vilnius Franciscan Conventuals monastery printing house: funds, sources of equipment and paper, building location, relations with employees and hired craftsmen, orders, sources of income, profitability. In order to better understand the specificity of the institutional press, an effort was made to establish a link between the research outcome and the wider context by addressing the question of the impact of both the society of the Grand Duchy of Lithuania and the Franciscan Order itself on the destiny of the printing house. In addition, the book of expenses and income reveals new biographical data about Vilnius engraver Franciszek Balcewicz.